Knowledge Attitude and Behaviors in Rational Antibiotics Drug Use of Nursing Students - Paokanha, Rraweewan; Thanyasawad, Thanyasiri; Yoochareonsuk, Kanchana (Journal of The Royal Thai Army Nurses, 2021)
The purpose of this research was to study of knowledge, attitudes behaviors of Rational Antibiotics Drugs Use and to examine the correlation among knowledge, attitudes and behaviors of Rational Antibiotics use. The 88 samples were nursing students purposive sampling. The research instruments were a test of knowledge and a questionnaire on the attitudes and behaviors regarding an appropriate use of drug. The item content validity for scale (S-CVI) was equivalent to 0.92. The Reliability of the questionnaire based on Cronbach’s Alpha was equivalent to 0.918 and the knowledge test based on the Kuder-Richardson Method was equivalent to 0.69. Data were analyzed by descriptive statistics. The research results were as follows. The sample group had a high degree of knowledge on Rational Antibiotics Drug use at ( = 0.78, SD. = 0.29). Attitudes and behaviors were moderate ( = 3.37, SD. = 0.99) and ( = 3.21, SD. = 1.17) The correlation among knowledge,attitudes and behaviors were negative moderate level (r = -.498, Sig = .000, r = -.427, Sig = .000). Attitudes and behaviors were positively high level (r = .558, Sig = .000). The recommendations were as follows.The activity model of teaching on antibiotic use should be adjusted in a realistic simulation. And practicing experience in real situations emphasis on attitude adjustment, which is likely to lead Nursing students to have correct and safe antibiotic behaviors.